PENGARUH MARKET VALUE TERHADAP HOLDING PERIOD SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Leleng, Ingrid Fransisca; Ilat, Ventje; Wokas, Heince (Universitas Sam Ratulangi, 2014)
Recognizing the need for consideration of an investor in making decisions to determine the ownership period (holding period) a share holding, it is very important for investors to understand the factors that affect stock holding period. The purpose of this study was to determine the effect of the Holding Period Market Value stocks. The analysis technique used is simple linear regression analysis. Based on the results of the study, that changes Holding Period for the 2010-2012 year only amounted to 14.651. The results of hypothesis testing and test f t test states H0 is accepted and Ha is rejected because the value obtained 0,748 > Î±= 0,05. The coefficient of determination ( R2 ) is equal to 0,004, giving the sense that the magnitude of Holding Period on Companies Food and beverages can be explained by the independent variables, Market Value is at 0.4 % while the remaining 99.6 % is explained by other variables not examined in the study this . Thus, the results of the testing in this study stated that the Market Value has no effect on the company's Holding Period.